Exploring a national book-gifting scheme: parents' and children's reactions - Wray, David; Medwell, Jane (Taylor & Francis, 2013)
Several early learning programmes have targeted children’s reading, particularly their relationships with books. One, Bookstart, provided free books to babies attending their 8-month health check at local clinics. Study of this programme suggested that it led to an improvement in language performance upon school entry. Booktime continues from Bookstart and involves the donation of a book pack to 5-year-old children in their first school term. This paper reports an evaluation of the impact of Booktime on the views about, and enjoyment of, reading, of participating children and on the views of parents/carers about helping their children with reading.